(untitled) (Bangladesh Journal of Zoology, 2024)
The IUCN Bangladesh has documented a total of 31 species belonging to the Pieridae family in Bangladesh. There is currently limited knowledge regarding the genetic diversity and molecular relationships among these butterflies. The present investigation involved the generation of mitochondrial COI (mtCOI) gene sequences for ten species of butterflies belonging to the Pierid family. After that, BLAST analysis showed 96% to 100% similarity, and then the sequences were submitted to NCBI’s GenBank. MEGA10 and BioEdit were used to identify a 584 bp COI gene fragment with 179 variable sites and 128 parsimony-informative sites. The COI sequences’ average base compositions were 38.56% T, 17.12% C, 30.18% A, and 14.12% G. While a significant AT bias (68.74%) existed among the Pierid species. The genetic distance between ten Pierid species was assessed using the Kimura 2-Parameter (K2P) algorithm, and the nucleotide differences ranged from 0.00172% to 0.24261%. Afterwards, the Maximum Likelihood (ML) method was used to construct a phylogenetic tree using ten sequences of Pierid species. These species belongs to two subfamilies, Pierinae and Coliadinae in Bangladesh. On the tree, the Pierinae subfamily of Pieridae formed a paraphyletic arrangement whereas the Coliadinae subfamily was shown to be monophyletic. The data analyses support the following relationships between the two subfamilies as follows: [(Appias + Leptosia) + (Pieris + Appias) + (Delias) + (Eurema + Catopsilia) + (Pareronia)]. This supported the theory that Pierinae and Coliadinae are sister taxa. Nonetheless, Pareronia hippia remains outside the main Pierinae group, requiring further study to resolve this issue. Finally, these studies generated ten mtCOI gene sequences that have the potential to serve as valuable references for the accurate identification of Pierid species. In addition, this result could be used in the future to reveal the subfamily relationships within the Pieridae taxonomic classification. Bangladesh J. Zool. 51(3): 289-299, 2023